Platform stabilization and load reduction of floating offshore wind turbines with tension‐leg platform using dynamic vibration absorbers - Wu, Zhongyou; Li, Yaoyu (Wind energy (Chichester, England), 2020)
Floating offshore wind turbines (FOWT) are subject to significant increases in structural loads due to the platform motion under turbulent wind and wave. The under‐actuation challenge in FOWT control demands for development of extra actuators for platform stabilization. For FOWT with tension‐leg platform (TLP), this paper presents a comprehensive study on design and control simulation for realizing active mooring line control via the deployment of vertically operated dynamic vibration absorbers (DVAs) at the spokes of TLP structure. The DVA is designed based on the suppression of the primary modes of platform pitch and roll motion. In addition to the enhancement of FAST‐based simulation module, an 11 degrees‐of‐freedom (DOFs) control‐oriented model is derived for the TLP‐FOWT‐DVA system. Based on the control‐oriented model, a linear quadratic regulator (LQR) controller is designed. Simulations are performed for 9 m/s and 18 m/s turbulent winds with different wind and wave directions. The wind turbine performance, platform motions, and structural fatigue loads are evaluated. The results show that the platform motion and tower loads in the lateral direction are significantly reduced, while the tower load in the fore‐aft direction can be moderately reduced. Also, significant reduction in the mooring line tension loads is observed. For achieving the performance in platform motion stabilization and load reduction, the average power consumption of the DVA actuators is less than 0.27% of the wind turbine power generated during the simulated periods. The figures of merits promise significant potential for the feasibility of DVA based control for TLP‐FOWT.